2021
DOI: 10.3390/electronics10131541
|View full text |Cite
|
Sign up to set email alerts
|

Object Identification and Localization Using Grad-CAM++ with Mask Regional Convolution Neural Network

Abstract: One of the fundamental advancements in the deployment of object detectors in real-time applications is to improve object recognition against obstruction, obscurity, and noises in images. In addition, object detection is a challenging task since it needs the correct detection of objects from images. Semantic segmentation and localization are an important module to recognizing an object in an image. The object localization method (Grad-CAM++) is mostly used by researchers for object localization, which uses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, Grad-CAM methods could be of use in various solutions, not only limited to explainable purposes. In [9], authors use generated CAMs as an intermediate step in a vision object detection model. According to the paper, the solution outperforms all the counterpart methods and can be used in unsupervised environments.…”
Section: Gradient-based Methodsmentioning
confidence: 99%
“…Moreover, Grad-CAM methods could be of use in various solutions, not only limited to explainable purposes. In [9], authors use generated CAMs as an intermediate step in a vision object detection model. According to the paper, the solution outperforms all the counterpart methods and can be used in unsupervised environments.…”
Section: Gradient-based Methodsmentioning
confidence: 99%
“…Taking advantage of this point, many studies have successfully applied this XAI technique. The research uses Grad-CAM++ with the Mask Regional Convolution Neural Network, which has shown a powerful real-time ability to detect and classify existing objects and shapes [24]. The research uses Grad-CAM++ enabled with the squeeze-and-excite network on the CT scan dataset of lung cancer [25].…”
Section: Related Workmentioning
confidence: 99%
“…Class activation map (CAM) is an intuitive method in convolutional neural network (CNN) interpretation, and it was usually generated by the last convolutional layer of a CNN, which can highlight different regions of the target class in the input image. To verify the contribution of CA-MobileNetV3 and CARAFE upsampling module to the count of wheat ears, an object localization method (Grad-CAM++) [32] was used to construct important regions of multiple objects on the image through gradients with convolutional layers for feature visualization. In this study, LWDNet and DM-Count were selected for feature visualization comparison, and the original wheat ear map, the wheat ear heat map of DM-Count and LWDNet, and the wheat ear visualization class heat activation map, were displayed, respectively, as shown in Figure 11.…”
Section: Existing Counting Challenges and Visualization Of Existing T...mentioning
confidence: 99%